2021
DOI: 10.1038/s41598-021-83022-5
|View full text |Cite|
|
Sign up to set email alerts
|

CXCR7 ameliorates myocardial infarction as a β-arrestin-biased receptor

Abstract: Most seven transmembrane receptors (7TMRs) are G protein-coupled receptors; however, some 7TMRs evoke intracellular signals through β-arrestin as a biased receptor. As several β-arrestin-biased agonists have been reported to be cardioprotective, we examined the role of the chemokine receptor CXCR7 as a β-arrestin-biased receptor in the heart. Among 510 7TMR genes examined, Cxcr7 was the most abundantly expressed in the murine heart. Single-cell RNA-sequencing analysis revealed that Cxcr7 was abundantly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…To reactivate CXCR7 signaling, we treated our cKO mice with the CXCR7 agonist TC14012, which attenuated the severe hypertrophic phenotype and improved heart function (see also Figure 7 ). As a potential downstream target for CXCR7 signaling, we identified increased pERK signaling, which has also been reported previously [ 54 , 57 , 59 ]. CXCL12 signaling directly via CXCR7 is Gαi-receptor-independent, and activation of pERK could lead to cell survival and chemotaxis [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…To reactivate CXCR7 signaling, we treated our cKO mice with the CXCR7 agonist TC14012, which attenuated the severe hypertrophic phenotype and improved heart function (see also Figure 7 ). As a potential downstream target for CXCR7 signaling, we identified increased pERK signaling, which has also been reported previously [ 54 , 57 , 59 ]. CXCL12 signaling directly via CXCR7 is Gαi-receptor-independent, and activation of pERK could lead to cell survival and chemotaxis [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, CXCR7 can also form heterodimers with the CXCR4 receptor regulating G-protein-mediated signal transduction [ 4 , 56 ]. A recent study has shown that CXCR7 expression is elevated in human heart failure and hypothesized that it might have cardioprotective effects [ 57 ]. Mechanistically the authors also demonstrated that CXCR7 acts through β-arrestin-mediated pERK signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, one can only speculate a few possibilities. Expression of ACKR3/CXCR7 is significantly increased at the infarct border zone of myocardium [ 26 , 27 , 28 ], and peri-infarct regions of the brain [ 29 ] in animal models [ 27 , 28 , 30 , 31 ] and humans alike [ 26 , 28 , 32 ]. Firstly, target organ (e.g., myocardium) specific expression of ACKR3/CXCR7 might either override or be complemented by the impact of platelet ACKR3/CXCR7 in the repair and regenerative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Since activated platelets infiltrate ischemia affected myocardium [ 5 , 7 , 33 , 34 ], they can actively regulate the balance between inflammation vs regeneration [ 7 ]. The extent to which platelet ACKR3/CXCR7 may influence this functional outcome, superseding the acclaimed regenerative drive of ACKR3/CXCR7 highly expressed in cardiomyocytes [ 26 ] and endothelial cells [ 27 ], is uncertain. Cardiomyocytes, like circulating platelets [ 22 ], exhibit increased expression of CXCL12/SDF1α following MI, which significantly influences the migration of CXCR4 and ACKR3/CXCR7 expressing cardiac stem cells with regenerative potential [ 35 ] as observed in murine models.…”
Section: Introductionmentioning
confidence: 99%